PERAN STRATEGIS SEKRETARIS DALAM MEWUJUDKAN ADMINISTRASI PERKANTORAN YANG SISTEMATIS DAN EFEKTIF (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In the era of digitalization and rapid organizational transformation, secretaries play a strategic role in ensuring that office administration operates systematically and effectively. This article aims to elaborate on the crucial role of secretaries in supporting smooth operations and achieving organizational goals through information management, technology implementation, and coordination of administrative activities. The writing method uses literature review and case study, specifically at PT PLN (Persero) Aceh Region. The study results show that secretaries not only perform administrative functions but also serve as communication liaisons, information technology managers, and strategic partners to leadership. To face complex challenges such as digitalization and multitasking, competency development and organizational support are key factors. Therefore, professional, adaptive, and skilled secretaries play a vital role in creating modern, efficient, and competitive office administration.